Pengaruh Gaya Kepemimpinan terhadap Kinerja Karyawan pada PT. XYZ Bandung - Lina Gunawan; Fifi Alifia; Widwi Handari Adji (Ekonomis: Journal of Economics and Business, 2022)
Each company must have a leader with his or her leadership style. Leadership style means a process in which a person influences another person or group in his or her efforts to achieve a particular goal has been identified between leaders and their employees, an effort to improve employee performance as a task for leaders to organize the use of leadership for an organization.This research aims to find out the influence of leadership style on Karayawan's performance at PT XYZ BandungThe research methods used are questionnaires, interviews and literature. The research sample was all employees of PT XYZ Bandung numbering up to 40 respondents.The results of the study using calculations of the correlation coefficient of 0.661 showed that the relationship of leadership style to employee performance had a significant impact the coefficient of determination was 47.3%The known influence of leadership styles was 47.7% while the remaining 56.3%.